2015
DOI: 10.1038/mtna.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Disruption in Induced Pluripotent Stem Cells Using CRISPR/Cas9 Provides Selective Resistance of Immune Cells to CCR5-tropic HIV-1 Virus

Abstract: The chemokine (C-C motif) receptor 5 (CCR5) serves as an HIV-1 co-receptor and is essential for cell infection with CCR5-tropic viruses. Loss of functional receptor protects against HIV infection. Here, we report the successful targeting of CCR5 in GFP-marked human induced pluripotent stem cells (iPSCs) using CRISPR/Cas9 with single and dual guide RNAs (gRNAs). Following CRISPER/Cas9-mediated gene editing using a single gRNA, 12.5% of cell colonies demonstrated CCR5 editing, of which 22.2% showed biallelic edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 50 publications
5
81
0
1
Order By: Relevance
“…All the modified iPSCs could differentiate into monocytes/macrophages and gain resistance to HIV-1 challenge [21]. Dual gRNAs resulted in doubled efficiency from 12.5% to 27% of cell colonies and 22.2% to 41% biallelic editing [22]. Delivery systems were recently discussed about in a comprehensive study on primary CD4+ T cell manipulation [23].…”
Section: Methods For Blocking the Entry Of Hiv-1 Into Cells Editing Cmentioning
confidence: 99%
“…All the modified iPSCs could differentiate into monocytes/macrophages and gain resistance to HIV-1 challenge [21]. Dual gRNAs resulted in doubled efficiency from 12.5% to 27% of cell colonies and 22.2% to 41% biallelic editing [22]. Delivery systems were recently discussed about in a comprehensive study on primary CD4+ T cell manipulation [23].…”
Section: Methods For Blocking the Entry Of Hiv-1 Into Cells Editing Cmentioning
confidence: 99%
“…Kang et al 9 reported that viral entry into immune cells can be blocked by the successful replacement of CCR5 gene in human stem cells using CRISPR/Cas9. Wang et al 10 reported that repairing the DNA fragmented by Cas9 by the error-prone repair machinery of the cell led to mutated sequences that disrupted the viral life cycle.…”
Section: Redesigning Nature: Use Of Cas/crispr In Genome Editingmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) are under investigation as well, with the idea that modified iPSCs could differentiate into hematopoietic cells. Ye et al and Kang et al both demonstrated efficient bilallelic disruption of CCR5 in iPSCs and additionally showed efficient differentiation of modified cells [25,26]. Along the same lines, mesenchymal stem cells have been gene edited and converted to CD34+ progenitor cells [27].…”
Section: Suppression or Disruption Of Hiv Co-receptorsmentioning
confidence: 99%